A Japanese plum breeding core collection capturing and exploiting genetic variation - Osorio, María; Ahumada, Sebastián; Infante, Rodrigo; Pacheco, Igor; Fiol, Arnau; Ballesta, Paulina (MDPI, 2025)
The optimal exploitation of genetic variability is essential for the success of breeding programs and for identifying quantitative trait loci (QTLs) in genetic association studies. These benefit from populations with a high number of individuals; however, they are expensive since extensive plant maintenance, characterization, and evaluation are required. Core collections offer a practical solution by reducing the number of individuals while representing the original diversity of the population. This study aimed to construct a core collection for Japanese plum to serve as pre-breeding material and enable genetic association studies for traits that are difficult to evaluate. Starting from a population of 1062 individuals genotyped by sequencing, genetic distance and allele coverage metrics were applied to construct several core collections. Genetic parameters and phenotype distribution comparisons allowed for the selection of a core collection of 108 individuals that maximized genetic variability while representative of the original population, confirmed by linkage disequilibrium and population structure analyses. Its usefulness was validated by successfully mapping flowering and maturity dates through marker–trait association. The core collection constructed here will help in the study of fruit quality traits and biotic and abiotic responses, ultimately generating molecular markers to assist the crop’s molecular breeding.
Keywords: Ciruelo japonés; Diversidad genética; Population structure; Marker–trait association